Analysis of Effectiveness of SSSC in Transmission Network using PI Controlled Technique - Jain A.; Yadav L.K.; Omer A.; Bhullar S. (My University, 2025)
Today's scenario of power industry is increasing in power demand and limiting in transmission infrastructure. The huge amount of power is transmitted every day over the transmission network. The extension in transmission line facilities may be restricted up to a certain instant due to various reasons like environmental issues, use of land etc. Regulatory pressures also play an important role in the extension of the transmission line and high initial cost can't be avoided. Hence, there are huge restrictions in the path of extension of the transmission line. Earlier due to unavailability of high speed switching semiconductor devices, the dynamic changes in the lines such as voltage suppression, apparent power flow control cannot be compensated immediately. So, in order to meet these issues, FACTS devices have been introduced. The most important member of this family is Static Synchronous Series Compensator (SSSC), which controls the voltage profile and apparent power flow in the line. In this paper, two machine model system with SSSC have been considered which is simulated in MATLAB/SIMULINK. Also, an improved PI (Proportional & Integral) controlled technique utilizing SSSC model has been introduced to improve the parameters such as voltage and apparent power flow in the line. A comparison of these parameters between a compensated and uncompensated line have been carried out and the results show that the distortion level is also at the satisfactory levels. © 2017 The Authors. Published by Elsevier Ltd.